Pragmatizácia slovenskej štylistiky digitálnej éry - OĽGA ORGOŇOVÁ; ALENA BOHUNICKÁ (Stylistyka)
In this study, we respond to the fact that the context of the scientific interpretation of the stylistic differentiation in communication is formed by the framework conditions of contemporary communication, characterized by tendencies such as mediatization, digitalization, and the gradual democratization of social processes. Functional styles are transformed under the influence of new media, which expand communication possibilities and, at the same time, relativize classic style-forming factors, especially objective ones such as author, environment, addressee, function. The expansion of the communication space of each style into the digital space significantly affects the functions it fulfills, the dynamics of genres (the transformation of traditional genres, the emergence of new genres and the disappearance of some traditional genres) and the qualitative transformation of styles (the form and stylistic values characteristic of expressions realized in individual spheres of communication change). The present study aims to clarify the shift in the division and reflection of the communication continuum in the stylistics of the last 50 years. This is achieved using the support of traditionally divided communication spheres: the sphere of ordinary communication, the sphere of professional communication, the sphere of institutional contact, the sphere of mass media communication, the commercial sphere, and the sphere of artistic creation. Furthermore, the study specifically addresses the spheres of rhetoric, which affect the entire communication continuum.